2021
DOI: 10.3390/ijms22031318
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of Autophagy in Treatment of Resistance Mechanisms in Glioblastoma

Abstract: Autophagy is a process essential for cellular energy consumption, survival, and defense mechanisms. The role of autophagy in several types of human cancers has been explicitly explained; however, the underlying molecular mechanism of autophagy in glioblastoma remains ambiguous. Autophagy is thought to be a “double-edged sword”, and its effect on tumorigenesis varies with cell type. On the other hand, autophagy may play a significant role in the resistance mechanisms against various therapies. Therefore, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 212 publications
(243 reference statements)
0
18
0
Order By: Relevance
“…13,[94][95][96] The intricate nature of autophagy regulation by radiotherapy and chemotherapy bears a fair deal of controversy and remains a subject for more studies, especially in the context of managing treatment resistance. 94,[97][98][99] Collectively, the integration of autophagy regulation into future therapeutic explorations for glial tumors appears to represent a perspective avenue.…”
Section: Discussionmentioning
confidence: 99%
“…13,[94][95][96] The intricate nature of autophagy regulation by radiotherapy and chemotherapy bears a fair deal of controversy and remains a subject for more studies, especially in the context of managing treatment resistance. 94,[97][98][99] Collectively, the integration of autophagy regulation into future therapeutic explorations for glial tumors appears to represent a perspective avenue.…”
Section: Discussionmentioning
confidence: 99%
“…These data confirm recent findings that have demonstrated a worse prognostic behavior in GBM patients with high levels of autophagy-related genes and MGMT promoter unmethylated ( 57 ). However, autophagy can have a tumor suppressor function in GBM destroying damaging unfolded proteins, oncogenic protein substrates, and injured organelles ( 58 , 59 ). Recently, it has been reported that elevated levels of ATGs were linked to better survival in glioma patients ( 60 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher mtDNA/nDNA ratio that we observed may be linked to increased mitochondrial turnover, as suggested by the observations that OXPHOS was better preserved in resistant cells and that the autophagy/mitophagy inhibitor CQ preferentially killed resistant cells in clonogenic assays. Inhibiting autophagy in general has been widely studied to treat chemoresistant GBM [ 43 ]. Buccarelli et al [ 44 ] linked it to mitochondrial quality control by showing that inhibition of autophagy with quinacrine, a compound that is able to cross the BBB, increased the susceptibility of GBM stem cells to TMZ by triggering ferroptosis.…”
Section: Discussionmentioning
confidence: 99%